2017
DOI: 10.1139/cjp-2016-0593
|View full text |Cite
|
Sign up to set email alerts
|

Periodic momentum and thermal boundary layer mixed convection flow around the surface of a sphere in the presence of viscous dissipation

Abstract: Numerical solutions for the periodic laminar boundary layer mixed convection flow around the surface of a heated sphere in the presence of viscous dissipation have been obtained by solving the governing equations using an implicit finite difference numerical technique. The fluid under consideration is assumed to be viscous and incompressible. Periodic momentum and thermal boundary layer profiles for different positions of x around the surface of the sphere are evaluated. The features of the obtained results fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Viscous dissipation effect usually is appreciated on convection with large decelerations from high rotating speeds, high-velocity flow and also in highly viscous flow with moderate velocity [25]. The study of the viscous dissipation effect gained the attention of many researchers recently by Ashraf et al, [26], Zokri et al, [27], Mohamed et al, [28] and Sharada and Shankar [29]. To the best of our knowledge, the present problem is never been considered before, so the results obtained in this study are new.…”
Section: Introductionmentioning
confidence: 99%
“…Viscous dissipation effect usually is appreciated on convection with large decelerations from high rotating speeds, high-velocity flow and also in highly viscous flow with moderate velocity [25]. The study of the viscous dissipation effect gained the attention of many researchers recently by Ashraf et al, [26], Zokri et al, [27], Mohamed et al, [28] and Sharada and Shankar [29]. To the best of our knowledge, the present problem is never been considered before, so the results obtained in this study are new.…”
Section: Introductionmentioning
confidence: 99%
“…The system of Equations (‐) subject to the boundary conditions (11), are solved by using Primitive Variable Formulation for Finite Difference Method numerically using Lahr Fortran‐95. The discretization process of governing equations are similar to one used Ashraf et al…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…Under the conditions given in (14), by dropping bars the aforementioned system of equations having the following:…”
Section: Mathematical Formulation Of the Flow Modelmentioning
confidence: 99%
“…It was found that viscous dissipation parameter, N, and amplitude-to-length ratio of wavy surface α accelerated the fluid velocity and temperature that slowed down the rate of heat transfer. Ashraf et al [14] numerically investigated the periodic momentum and thermal boundary-layer mixed convection flow and oscillating convection flow [15] at various angles of a sphere in the presence of viscous dissipation. Authors [16][17][18][19][20][21], have studied the different cases of heat and mass transfer by using some new trends of solution.…”
Section: Introductionmentioning
confidence: 99%